Integrasi Islam dan Sains di Universitas Islam Internasional Malaysia dan Islamabad - Husin, Malik; Yusrianto, Edi; Yasin, Arbi (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to analyze the implementation of the integration between Islam and science within the higher education curricula of two prominent institutions: the International Islamic University Malaysia (IIUM) and a higher education institution in Islamabad. Using a qualitative approach with a comparative case study method, data were collected through document analysis, semi-structured interviews with faculty and curriculum developers, and classroom observations. The findings reveal that IIUM adopts a holistic approach through the concept of the Islamization of Knowledge, while the Islamabad institution emphasizes the connection between scientific discoveries and Islamic values by strengthening ethics-based curricula. Although both institutions demonstrate a strong commitment to integration, they face challenges such as secular paradigm resistance, limited resources, and the lack of systematically supportive literature. The implications of this study highlight the importance of collaborative curriculum design involving scientists and Islamic scholars, as well as the development of practical integrative models to ensure Islamic higher education produces both competent and ethically grounded scholars